Kirab Tumpeng Nusantara as a Form of Religious Moderation in Buling Hamlet, Bubakan Village, Girimarto District - Girlnanda Yansi Talenta (Javanologi: International Journal of Javanese Studies, 2024)
This study aimed to determine Kirab Tumpeng Nusantara as a form of religious moderation in the Buling hamlet community based on the functional, structural theory of Talcott Parsons. This qualitative research approach uses descriptive analysis with observation, interview, and literature study methods. The material object is Kirab Tumpeng Nusantara as a form of religious moderation of the Buling hamlet community and the formal object of the functional, structural approach of Talcott Parsons. Talcott Parsons' theory is that society as a system is interconnected and interdependent. The most important factor of a social system integration is agreement. Later Talcott Parsons developed the concept of functional imperatives to make systems last. This imperative concept is commonly referred to as AGIL, which stands for Adaptation, Goal attainment, Integration, and Latency. The determination of the main goal of Kirab Tumpeng Nusantara as a form of Religious Moderation of the Buling hamlet community and its surroundings, then the adaptation stage as a process of Islamic religious groups in accepting Kirab Tumpeng Nusantara which, in fact is identical to Buddhist celebrations in order to achieve Religious Moderation, the third is the integration stage, which is the stage of adjusting Religious Moderation through tolerance and mutual assistance at the Kirab Tumpeng Nusantara ceremony, and the fourth is Latency, which is maintenance so that religious moderation can be sustainable or carried out continuously so that people have a balanced life.